2020
DOI: 10.1186/s12881-020-01098-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of PNPLA3 rs738409 G/C gene polymorphism with nonalcoholic fatty liver disease in children: a meta-analysis

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease worldwide. Current studies have shown that PNPLA3 (Patatin-like phospholipase domain containing 3) rs738409 G/ C gene polymorphism is associated with adult nonalcoholic fatty liver disease [1, 2].But there is no consensus on the relationship between PNPLA3 rs738409 G/C gene polymorphism and children NAFLD due to differences in population samples. To this end, a meta-analysis of published research is c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…21 Recently in children, Tang et al showed that the G allele was associated with 3 times the odds of having NAFLD compared to the C allele. 22…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…21 Recently in children, Tang et al showed that the G allele was associated with 3 times the odds of having NAFLD compared to the C allele. 22…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…Over the last several years, meta-analyses of PNPLA3 I148M carriers versus noncarriers repeatedly conclude that carriers of the variant allele are at increased risk for all stages of NAFLD, including NASH, cirrhosis, and HCC [6,7,65,[72][73][74][75], among the pediatric and adolescent population [2,76], and among lean individuals with NAFLD [77]. NASH is emerging as the leading cause of liver transplant in the developed world.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty liver pathophysiology includes a well-known spectrum of determinants such as inflammation, IR, genetics and environment[ 4 , 28 , 29 ]. Genetic determinants commonly implied in NAFLD susceptibility (such as PNPLA3 [ 30 - 32 ], TM6SF2 [ 33 ], MBOAT7 [ 34 - 36 ] and HSD17B13 [ 37 - 42 ] genes) have been also linked to MAFLD pathogenesis[ 43 - 45 ] (Table 2 ). In particular, the effect of the PNPLA3 I148M polymorphism as a key genetic factor for NAFLD susceptibility across different ethnicities has been largely recognized both in adults and children[ 45 ].…”
Section: Pathophysiologymentioning
confidence: 99%